Ultra-early neurological deterioration following a brain arteriovenous malformation rupture - Shotar, Eimad; Chiaroni, Pierre-Marie; Haffaf, Idriss; Cortese, Jonathan; Jacquens, Alice; Garzelli, Lorenzo; Allard, Julien; Elhorany, Mahmoud; Amouyal, Caroline; Mathon, Bertrand; Nouet, Aurélien; Premat, Kévin; et al. (Frontiers in Neurology, 2024)
Purpose This study aims to explore the impact of ultra-early neurological deterioration (U-END) on the outcome (mortality and poor neurological status) following a brain arteriovenous malformation (BAVM) rupture and identify determinants of U-END. Methods Patients with BAVM ruptures admitted to a single tertiary care center were retrospectively reviewed. U-END was defined as a worsening by two or more points on the Glasgow Coma Scale (GCS). U-END was tested as a potential predictor of in-hospital mortality and poor outcomes. Univariate and multivariate analyses were performed to identify determinants of U-END. Patients with U-END were also matched and compared with BAVM rupture controls presenting with a GCS close or equal to either their initial or their lowest GCS. Results A total of 248 patients with BAVM ruptures met the inclusion criteria, with 39 (15.7%) patients presenting with U-END. U-END was not associated with and was not an independent predictor of in-hospital mortality (12.8 vs. 10.5% in the rest of the study population; p = 0.67) or poor outcomes (39.5 vs. 36.9%; p = 0.77). The only independent determinants of U-END were hydrocephalus (OR 2.6 [95%CI, 1.1–6.4]; p = 0.03) and intraventricular hemorrhage (IVH; OR 3.5 [95%CI, 1.1–11.7]; p = 0.04). When compared to the initial GCS control group, U-END patients more often presented with IVH (89.5 vs. 64.1%; p = 0.009) and hydrocephalus (73 vs. 38.5%; p = 0.003). When compared to the lowest GCS control group, U-END patients had lower early S100B serum levels (0.35 ± 0.37 vs. 0.83 ± 1; p = 0.009) and a lower rate of poor outcome (39.5 vs. 64.9%; p = 0.03). Conclusion Ultra-early neurological deterioration in ruptured BAVMs did not result in increased mortality or poor outcomes and was most often related to IVH and hydrocephalus.